2015
DOI: 10.1073/pnas.1507704112
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric interactions between agonists and antagonists within the adenosine A 2A receptor-dopamine D 2 receptor heterotetramer

Abstract: Adenosine A 2A receptor (A 2A R)-dopamine D 2 receptor (D 2 R) heteromers are key modulators of striatal neuronal function. It has been suggested that the psychostimulant effects of caffeine depend on its ability to block an allosteric modulation within the A 2A R-D 2 R heteromer, by which adenosine decreases the affinity and intrinsic efficacy of dopamine at the D 2 R. We describe novel unsuspected allosteric mechanisms within the heteromer by which not only A 2A R agonists, but also A 2A R antagonists, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
222
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(233 citation statements)
references
References 29 publications
7
222
0
4
Order By: Relevance
“…In these experiments we found that the presence of the A 2A R agonist CGS 21680 changed the dissociation constant of the radiolabelled A 2A R antagonist [ 3 H]ZM 241385 [21]. This constant did not change in the presence of several A 2A R antagonists, such as caffeine or SCH 58261 (Table 1).…”
Section: Homodimeric Nature Of Both a 2a R And D 2 Rmentioning
confidence: 79%
See 2 more Smart Citations
“…In these experiments we found that the presence of the A 2A R agonist CGS 21680 changed the dissociation constant of the radiolabelled A 2A R antagonist [ 3 H]ZM 241385 [21]. This constant did not change in the presence of several A 2A R antagonists, such as caffeine or SCH 58261 (Table 1).…”
Section: Homodimeric Nature Of Both a 2a R And D 2 Rmentioning
confidence: 79%
“…modulation of ligandbinding properties, is the ability of A 2A R agonists to decrease the affinity of dopamine D 2 receptor (D 2 R) for its agonists in the A 2A R-D 2 R heteromer [17][18][19][20][21]. A 2A R-D 2 R heteromers have been found in transfected cells [22,23], primary cultures of striatal neurons [22] and, in situ, in mammalian striatum [21,[24][25][26], where they play an important role in the modulation of GABAergic striato-pallidal neuronal function [24,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for heterotetramer formation was obtained by using BRET with double BiLC and BiFC assays (15,16). In this assay, the two BRET sensors, the donor Rluc8 (a more efficient variant of Rluc) and the acceptor YFP Venus (a more efficient variant of YFP), are split into two hemiproteins, with each split sensor being fused to one of the four putative interacting receptors.…”
Section: And D)mentioning
confidence: 99%
“…The chronic use of CFE may reduce dopamine release via the stimulation of A1-A2A heterodimer in the axon terminal of glutamate neurons and leads CFE tolerance. CFE antagonizes A2A receptor in the ventrolateral preoptic area and reduces inhibitory neurotransmission, especially gamma-amino butyric acid (GABA) to the tuberomammillary nucleus, a histaminergic projection nucleus, activation of which may promote the arousal effect of it (Bonaventura et al, 2015). CFE, otherwise, through its phosphodiesterase inhibitory potential, augments the intracellular cyclic AMP (cAMP), and activates protein kinase-A (PK-A), downregulates tumor necrosis factoralpha (TNF-α) and leukotriene synthesis along with a reduction of inflammation and innate immunity.…”
Section: Mechanisms Invonvedmentioning
confidence: 99%